Equilibrium Selection in Experimental Cheap Talk Games - Adrian de Groot Ruiz; Theo Offerman; Sander Onderstal (Tinbergen Institute, 2015)
In the past, many refinements have been proposed to select equilibria in cheap talk games. Usually, these refinements were motivated by a discussion of how rational agents would reason in some particular cheap talk games. In this paper, we propose a new refinement and stability measure that is intended to predict actual behavior in a wide range of cheap talk games. According to our Average Credible Deviation Criterion (ACDC), the stability of an equilibrium is determined by the frequency and size of credible deviations. ACDC organizes the results from several cheap talk experiments in which behavior converged to equilibrium, even in cases where other criteria do not make a prediction.
Keywords: C72; C92; D82; D83; 330; Cheap talk; Neologism proofness; Credible deviation; Refinement; ACDC; Experiment